THE INFLUENCE OF PRODUCT COMPLETENESS, PRICE, AND LOCATION ON CONSUMER PURCHASE DECISIONS PUSH PIN SHOP BANDAR LAMPUNG (SURVEY AT PUSH PIN STORE BANDAR LAMPUNG): PENGARUH KELENGKAPAN PRODUK, HARGA, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN BANDAR LAMPUNG (SURVEI PADA KONSUMEN TOKO PUSH PIN BANDAR LAMPUNG) - Mawarni, Alida; Agung, Maulana; Subagja, Ghia (Jurnal Kompetitif Bisnis, 2023)
This study aims to determine the effect of product completeness, price, and location on consumer purchasing decisions at push pin shops in Bandar Lampung. This research is a type of Explanatory Research with a quantitative approach. The sampling technique is using the purposive sampling technique using the Non-Probability Sampling method with a sample of 100 respondents from push pin shop consumers. Analysis of the data in this study using multiple linear regression analysis with the help of SPSS 26. The results of this study indicate that the completeness of the product, price, and location simultaneously affect the purchase decision by 60.8%. While the partial test results of each variable indicate that the completeness of the product has a positive and significant effect on purchasing decisions by 3.71%, the price has a positive and significant effect on purchasing decisions by 5.21% and location has a negative and insignificant effect on purchasing decisions by - 0.56%. The biggest influence lies in the product completeness variable, seen from the availability of various brands, the availability of products at the store makes consumers consider buying a product at the store.